Sinergi Teknologi dalam Kurikulum Pembelajaran yang Positif (Studi pada Sekolah Harapan Mulia Bali) - Suweta, I Made (Jayapangus Press, 2023)
Education is one of the key aspects of nation-building. In the 21st century information technology era, the integration of technology into the educational curriculum has become an increasingly important issue. This article examines the synergy of technology integration in the Merdeka Curriculum at Harapan Mulia School in Bali as an effort to improve the quality of education in Indonesia. This research aims to analyze the process and implementation of technology integration in the educational curriculum at Harapan Mulia School in Bali. This research uses a qualitative descriptive method. The results of the research show that the synergy of technology integration in the Merdeka Curriculum at Harapan Mulia School in Bali has great potential to enhance the quality of education. Technology integration opens up opportunities for more creative and effective learning strategies. The synergy of technology integration in the Merdeka Curriculum at Harapan Mulia School in Bali has significant potential to improve the quality of education in Indonesia. Technology integration provides opportunities for more creative and effective learning strategies. Support from the government, school supervisors, and teacher training is key to the successful implementation of technology in the curriculum. Hopefully, this will be a significant breakthrough in enhancing the quality of.